A framework for graceful interaction for web interface design / Wan Norizan Wan Hashim - Wan Hashim, Wan Norizan (Institute of Graduate Studies, UiTM, 2016)
It is argued that the design of life experiences with digital artifact should be aligned with the rich experience of the physical sensory life. The emphasis of functionality and efficiency of digital artifact is currently being infiltrated with new design criteria such as friendliness, playfulness, aesthetically pleasing and emotionally satisfying. Designing for aesthetic interaction is designing for a beauty that is rewarding in itself leading to aesthetic experience, which involves bodily skills and emotional sensitivity. Following the argument that form in an aesthetic experience has deep roots in organic bodily rhythms and the social conditions which help structure them, we conceptualize graceful interaction as a form to enrich user experience. Using the design science approach, graceful interaction is conceptualized through the abstraction of graceful dance movement that was derived from an interview with an art performance expert. The graceful dance movement elements is then mapped into the set of graceful interaction design elements obtained from the integration of Laban Effort Movement Theory with effort qualities of movement by Bacigalupi. This mapping is the basis of the prescription of the graceful interaction design framework that also encompasses the criteria of movement quality. The framework was then validated through experimental work…